An Insight into Professional Identity Formation: Qualitative Analyses of Two Reflection Interventions During the Dissection Course. Issue 3 (4th October 2019) - Shiozawa, Thomas; Glauben, Markus; Banzhaf, Michael; Griewatz, Jan; Hirt, Bernhard; Zipfel, Stephan; Lammerding‐Koeppel, Maria; Herrmann‐Werner, Anne
Abstract : The professional behavior of future doctors is increasingly important in medical education. One of the first subjects in the curriculum to address this issue is gross anatomy. The Tuebingen Medical Faculty implemented a learning portfolio and a seminar on medical professionalism during the dissection course. The aims of this research project are to get an overview of how students form a professional identity in the dissection course and to compare the content of both their oral and written reflections on the course. A qualitative analysis was conducted of the oral and written reflections on the dissection laboratory experience. This study was conducted during winter term 2013/2014 with a cohort of 163 participants in the regular dissection course. Written reflection texts (from n  = 96 students) and audio recordings from four oral reflection seminar discussions (with n  = 11 students) were transcribed and deductively categorized with Mayring's qualitative content analysis method. Both qualitative analyses show that students reflected on many topics relevant to professional development, including empathy, respect, altruism, compassion, teamwork, and self‐regulation. Quantitative analysis reveals that students who attended the oral reflection wrote significantly more in their written reflection than students who did not. There is, however, no difference in the reflection categories. Reflection content from students corresponds with categories derived from existing competency frameworks. Both the seminar (oral reflections) and the learning portfolio (written reflections) present excellent opportunities to foster professional development during anatomy education; the key is using them in conjunction with the dissection course.